2010
DOI: 10.3109/09638288.2010.511420
|View full text |Cite
|
Sign up to set email alerts
|

Heart rate autonomic responses during deep breathing and walking in hospitalised patients with chronic heart failure

Abstract: Deep breathing exercises and walking are safe and promote beneficial effects on heart rate variability in patients hospitalised for CHF.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 36 publications
(39 reference statements)
1
3
0
Order By: Relevance
“…Low values of vagal indices and high values of sympathetic modulation were found in stable patients with moderate HF in all three conditions. These findings are consistent with other studies using portable ECGs and heart rate monitors [8, 24, 25]. The present study showed that short-term HRV indices are stable and reproducible using Holter and PolarS810i at rest because, as expected, the capturing and editing of stationary signals facilitate HRV analysis in stable conditions.…”
Section: Discussionsupporting
confidence: 93%
“…Low values of vagal indices and high values of sympathetic modulation were found in stable patients with moderate HF in all three conditions. These findings are consistent with other studies using portable ECGs and heart rate monitors [8, 24, 25]. The present study showed that short-term HRV indices are stable and reproducible using Holter and PolarS810i at rest because, as expected, the capturing and editing of stationary signals facilitate HRV analysis in stable conditions.…”
Section: Discussionsupporting
confidence: 93%
“…In the time domain, the R-R intervals were analyzed by the root-mean square differences of successive R-R intervals (RMSM) and mean of the standard deviations for all R-R intervals (RMSSD) indices. The RMSM index corresponded to the square root of the sum of the square of the differences of the individual values in relation to the mean value, divided by the number of R-R intervals in a specified time period [ 26 ] . The RMSSD corresponded to the square root of the sum of the square of the differences between the R-R intervals registered, divided by the number of R-R intervals in a specified time period less one [ 26 ] .…”
Section: Methodsmentioning
confidence: 99%
“…The RMSM index corresponded to the square root of the sum of the square of the differences of the individual values in relation to the mean value, divided by the number of R-R intervals in a specified time period [ 26 ] . The RMSSD corresponded to the square root of the sum of the square of the differences between the R-R intervals registered, divided by the number of R-R intervals in a specified time period less one [ 26 ] . To the frequency domain analysis, 256 points of the four minutes (endurance protocol) was selected as the criterion required for application of the spectral methods (i.e., Fast Fourier Transforming).…”
Section: Methodsmentioning
confidence: 99%
“…Entropy indices are seen as a potential marker by which to assess the benefits of exercise [ 7 , 14 , 18 , 19 ]. In one study, the SDNN, RMSSD, ApEn and SampEn values of patients with chronic heart failure were shown to be significantly lower than those of healthy controls during walking [ 20 ]. In another study, the ApEn values of 250 patients with heart failure (≥65 years old) were significantly lower than that of 100 age-matched controls in ECGs recorded over a period of 24 h [ 21 ].…”
Section: Introductionmentioning
confidence: 99%